Animals at work - Fitzgerald, John D.; Smith, Ronald Ronald James; Pye Andersen Ltd. (London Pye Andersen Ltd., 1994)
This informative book explores the many roles that animals play in the world of work$1 (Bfrom guide dogs and police horses to elephants used in construction and oxen used in farming. Illustrated with engaging photographs, the book provides insight into animal intelligence and human-animal collaboration.s
Includes facts, photos, and short descriptions of how animals assist humans in various jobs and environments.
b
Keywords: Working animals -Animal behaviour-Human-animal relationships-Animals$1 (BEmployments